Structural insights into viral genome replication by the severe fever with thrombocytopenia syndrome virus L protein. Issue 3 (18th January 2023) - Williams, Harry M; Thorkelsson, Sigurdur R; Vogel, Dominik; Milewski, Morlin; Busch, Carola; Cusack, Stephen; Grünewald, Kay; Quemin, Emmanuelle R J; Rosenthal, Maria
Abstract: Severe fever with thrombocytopenia syndrome virus (SFTSV) is a phenuivirus that has rapidly become endemic in several East Asian countries. The large (L) protein of SFTSV, which includes the RNA-dependent RNA polymerase (RdRp), is responsible for catalysing viral genome replication and transcription. Here, we present 5 cryo-electron microscopy (cryo-EM) structures of the L protein in several states of the genome replication process, from pre-initiation to late-stage elongation, at a resolution of up to 2.6 Å. We identify how the L protein binds the 5′ viral RNA in a hook-like conformation and show how the distal 5′ and 3′ RNA ends form a duplex positioning the 3′ RNA terminus in the RdRp active site ready for initiation. We also observe the L protein stalled in the early and late stages of elongation with the RdRp core accommodating a 10-bp product-template duplex. This duplex ultimately splits with the template binding to a designated 3′ secondary binding site. The structural data and observations are complemented by in vitro biochemical and cell-based mini-replicon assays. Altogether, our data provide novel key insights into the mechanism of viral genome replication by the SFTSV L protein and will aid drug development against segmented negative-strand RNA viruses.